2010
DOI: 10.2189/asqu.2010.55.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Nexus Work: Brokerage on Creative Projects

Abstract: This study examined how brokers on creative projects integrate the ideas of others. We use the term "nexus work" to refer to brokerage requiring synthesis or integration, rather than just communication or transference of ideas. With an ethnographic investigation of 23 independent music producers in the Nashville country music industry, we examined how producers in the brokerage role fostered the integration of others' contributions throughout four phases of the creative process. We discovered that ambiguity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
302
0
16

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 454 publications
(328 citation statements)
references
References 78 publications
10
302
0
16
Order By: Relevance
“…Overall, we found that the effective size of an affiliation increases with its awarded funds ( Fig. 2A), with the top-funded universities occupying brokerage positions between otherwise disconnected affiliations, potentially playing a key role in developing new access to information and opportunities (19,27,28).…”
Section: Significancementioning
confidence: 94%
“…Overall, we found that the effective size of an affiliation increases with its awarded funds ( Fig. 2A), with the top-funded universities occupying brokerage positions between otherwise disconnected affiliations, potentially playing a key role in developing new access to information and opportunities (19,27,28).…”
Section: Significancementioning
confidence: 94%
“…Brokers are used on some creative projects to integrate diverse ideas and perspectives [54]. These brokers may exclude certain individuals from participating in order to avoid premature convergence, in effect maintaining diverse viewpoints by decreasing the frequency of interaction [54].…”
Section: Predicting Optimal Interaction Frequencymentioning
confidence: 99%
“…Indeed, recent research on MNEs indicates that managers' boundary-spanning activities matter with regard to strategic renewal of business units Wooldridge et al 2008). Boundaryspanning ties are instrumental in linking multiple sources of diverse knowledge that may be useful to innovation (Hansen et al 2005;Lingo and O'Mahony 2009;Obstfeld 2005). Defined as activities through which new knowledge and expertise are sought from other units (Hansen 1999), boundary-spanning is a potential key driver of exploratory innovation.…”
Section: Boundary-spanning and Strategic Renewalmentioning
confidence: 99%